An Efficiency and economic viability of water management in the production of table tomatoes - Vieira, Carlos Luiz; Ponce, Franciely da Silva; Campos, Renê Arnoux da Silva; Queiroz, Tadeu Miranda de; Dallacort, Rivanildo; Seabra Júnior, Santino (Comunicata Scientiae, 2024)
Tomato (Solanum lycopersicum L.) cultivation can be expensive, with costs exceeding BRL 100,000 per hectare, which drives the search for tactics that reduce costs. Consequently, strategies have been developed to make it viable in tropical regions and areas with water scarcity. The objective was to evaluate the cost and profitability of water management in table tomato cultivation under different irrigation schedules. This study was carried out using the Fascínio tomato hybrid and four irrigation management approaches (no cutting, 100, 105, and 110 days after sowing, DAS). Harvesting was conducted four times, and the averages were summed toCOE estimate the total and commercial production, as well as the losses, for each irrigation schedule. To calculate the cost, both the effective and total operational costs were considered, referring to the establishment of the crop and to each irrigation cut used. Several economic indicators were calculated, including gross income (), operating profit (), profitability index (%), gross margin (), break-even point (kg), and price break-even point (/kg). The cost of water for irrigation had little impact on Effective Operating Cost (EOC) and Total Operating Cost (TOC); however, the treatment without cutting irrigation provided greater total and commercial production, which reflected the profitability parameters (OP, PI, GM, break-even point, and price break-even point). The treatment without cutting irrigation was 0.13%, 0.19%, and 0.024% more profitable than the treatments with irrigation cuts at 110, 105, and 100 DAS, respectively. This increase in profitability was justified due to the higher productivity, justifying the maintenance of irrigation in tomato cultivation. The treatment without cutting irrigation provided the highest total and commercial productivity of tomato fruits, with 8099.58 and 7927.36 units, respectively, generating a higher gross revenue of 32,398.32.